2017
DOI: 10.1590/2317-1545v39n2176874
|View full text |Cite
|
Sign up to set email alerts
|

Physiological performance of wheat seeds treated with micronutrients and protection products during storage

Abstract: -Seeds with high quality are one of the important factors to consider in the crops establishment on field. Therefore, the physical and physiological quality of wheat seeds treated with mixes of micronutrients including zinc and protective products were aimed. The wheat seeds were analyzed in a factorial scheme 5x3x4, with five storage time: 0, 60, 120, 180 and 240 days; three micronutrients: micronutrients 1 (1% Mn; 0.1% Mo; 10% Zn); micronutrients 2 (0.3% B; 0.3% Co; 3% Zn) and no micronutrients, and four pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
2
1
2
Order By: Relevance
“…However, the hermetic system provided a higher percentage of normal seedlings, when compared to the conventional system, throughout the storage period. These results are in agreement with those found by Freiberg et al (2017), who observed an increase in the values of the first germination count of wheat seeds up to 120 days of conventional storage, after which the values were also reduced. Harvest delay negatively influenced the first germination count values for both storage systems, corroborating the results observed by Tunes et al (2010a), in barley seeds, with harvest delay.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the hermetic system provided a higher percentage of normal seedlings, when compared to the conventional system, throughout the storage period. These results are in agreement with those found by Freiberg et al (2017), who observed an increase in the values of the first germination count of wheat seeds up to 120 days of conventional storage, after which the values were also reduced. Harvest delay negatively influenced the first germination count values for both storage systems, corroborating the results observed by Tunes et al (2010a), in barley seeds, with harvest delay.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained by Rupollo et al (2004) and Petrenko (2014), studying oat and wheat seeds, which verified an increase in seed germination during the hermetic storage, with a subsequent reduction in germination at 180 and 360 days of storage, respectively. Freiberg et al (2017) also verified a reduction in the germination percentage of wheat seeds during 240 days under conventional storage.…”
Section: Resultssupporting
confidence: 52%
“…Environments with temperature and humidity control favor the seed physiological quality, whereas small changes in the moisture content reduce the metabolic activity and the deterioration rate of seeds (Cardoso et al 2012). Contrary to differences observed between the treatments in this study, Freiberg et al (2017) found no effect of treatment on the moisture content of wheat seeds treated with a combination of micronutrients, polymer, fungicide and insecticide, stored for 6 months under uncontrolled conditions of temperature and humidity.…”
Section: Resultscontrasting
confidence: 89%
“…For wheat, Hossen et al (2014) reported higher germination percentages in seeds treated with thiamethoxam and thiamethoxam + carboxin + thiram. Similarly, the seed treatment with carboxin + thiram + thiamethoxam and polymer + carboxin + thiram + thiamethoxam did not compromise the physiological quality of wheat seeds stored for 120 days under uncontrolled conditions of temperature and humidity (Freiberg et al 2017).…”
Section: Resultsmentioning
confidence: 88%
“…They pointed out that their active ingredients interacted with the embryo, which resulted in a significant decrease in seed vigor and seed germination percentage, which was not observed in this research with use of the fungicide or with the chitosan coatings with fungicide. Freiberg et al (2017a) reported toxicity in a coating with the polymer 'Colorseed He' mixed with fungicide (Vitavax® Thiram 200 SC) and an insecticide (Thiamethoxam) in wheat seeds in storage at 180 days showing a low percentage of germination and an increase in the number of abnormal seedlings, unlike what was observed in this research. In general, insecticides have greater phytotoxicity than fungicides in soybean stored seeds (Carvalho et al, 2020;Rocha et al, 2020).…”
Section: Storage Of Chitosan Coated Seeds Mixed With Fungicidecontrasting
confidence: 86%